1991
DOI: 10.1242/dev.111.4.983
|View full text |Cite
|
Sign up to set email alerts
|

The snail gene required for mesoderm formation in Drosophila is expressed dynamically in derivatives of all three germ layers

Abstract: The zygotic effect gene snail (sna) encodes a zinc-finger protein required for mesoderm formation in Drosophila embryos. By in situ analysis, sna transcripts are first detected at syncytial blastoderm and persist until very late stages of embryogenesis. Expression of sna is transient and is observed in tissues derived from all three germ layers. Prior to germband elongation, sna RNA accumulation is consistent with its genetically determined role in mesoderm formation. Starting at germband elongation, a second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Snail was first identified in Drosophila melanogaster [ 13 ], and was found to be essential for mesoderm formation during gastrulation [ 14 ]. Subsequently, presence of two additional Snail family proteins, namely escargot and worniu, were established in the fruit fly.…”
Section: Master Regulators Of Emtmentioning
confidence: 99%
“…Snail was first identified in Drosophila melanogaster [ 13 ], and was found to be essential for mesoderm formation during gastrulation [ 14 ]. Subsequently, presence of two additional Snail family proteins, namely escargot and worniu, were established in the fruit fly.…”
Section: Master Regulators Of Emtmentioning
confidence: 99%
“…Mad is a member of SMAD family, and has been found mediating TGF-β signaling to regulate cell proliferation, differentiation and embryonic patterning during Drosophiladevelopment (Grandori et al, 2000;Raftery & Sutherland, 1999;Zheng et al, 2003). The other significantly enriched motif for H3K4me3, the GCA-rich motif, is similar to the sna motif from Snail superfamily that plays a key role in facilitating mesoderm differentiation (Alberga et al, 1991;Boulay et al, 1987;Leptin, 1991;. We also identified an important motif for H3K27me3 peaks, 'ACAT', which is homologous to Cf2 (Chorion factor 2) in Drosophila .…”
Section: Motif Analysis Of H3k4me3 and H3k27me3 In B Dorsalismentioning
confidence: 99%
“…Current evidence has revealed that FOXO (forkhead box class O) transcription factors (TF) regulate autophagy via transcriptional or post-translational mechanism, [9] yet whether other TF could cooperate with FOXO to trigger autophagy via transactivation of autophagy target genes remains unknown. The Snail family of zinc-finger TFs, first discovered in Drosophila, [10] have been well-characterized as transcriptional repressors to modulate epithelial-to-mesenchymal transition (EMT) in cancer progression, and growing evidence shows that Snail TFs also play pivotal roles in development, immunity, and metabolism. [11,12] In our recent publication, [13] we identified a coherent FOXO-SNAI feed-forward loop (FFL) in autophagy, which is evolutionarily conserved from Drosophila to human.…”
Section: Introductionmentioning
confidence: 99%